Pengaruh Pengembangan Karir dan Gaya Kepemimpinan terhadap Kinerja Guru dengan Organizational Citizenhsip Behavior sebagai Variabel Mediasi (Study pada Guru Sekolah Menengah Kejuruan) - Rizky Pradana Lutfiyanto; Nurul Huda; Hulmansyah Hulmansyah (Journal of Economics and Business Aseanomics (JEBA), 2020)
The purpose of this research is analyzing factors affect the performance education gap in vocational school occurring in jakarta regional. Data processing respondents were with the structural equation modeling (SEM) using all the tools of statistical product and service solution (SPSS) linear and that structural (LISREL). The data using the spread of the respondents in as many as 222 teacher vocational schools in jakarta. The information can be taken by direct observation several schools. The result showed that career development significant impact on citizenship as the organizational behavior t-hitung t-tabel (4,26 1,96). Significant impact on career development performance of teachers because the value of t-hitung t-tabel (2,88 1,96). A style of leadership significant impact on citizenship as the organizational behavior t-hitung t-tabel. A style of leadership significant impact on the performance of teachers because t-hitung t-tabel ( 2,58 1,96 ).Citizenship organizational behavior influences on teacher performance as the t-hitung   t-tabel ( 4,53 1,96 ).Citizenship and organizational behavior as variable mediation can perform the role well by adding on the influence the every variable